Research Publication Trends among Physicists of the Indian Institute of Science and the University of Kerala: A Bibliometric Study (International Journal of Information Dissemination and Technology, 2013)
The bibliometric study analysed the research productivity of physicists at the Indian Institute of Science (IISc) and the University of Kerala (KU) during 2004-2008. The paper gives a summary and review of the various research evaluation studies of institutions and disciplines. There were 352 research articles listed in the Physics doctoral theses of both the institutions, including 267 from the IISc and 85 from the KU. The authorship trend is towards multi-authored papers in IISc and solo research is predominant in the KU The degree of collaboration of publication was calculated to be 0.94 in IISc researchers and 0.40 in the case of the KU. Journals are the most preferred channel of publication of IISc researchers while KU researchers prefer to publish their research findings mostly in national seminars. The study shows that the Phys. Rev. B tops the list of IISc physicists' choice of journals for publication with 16 publications (9.58%). The KU researchers prefer to publish their research results mostly in Indian journal of Radio and Space Physics with 10 articles 25.64%. Elsevier Science publisher is the most common publisher preferred by the Physicists of both institutions.